Frequency of limb salvage after infra-inguinal bypasses for chronic limb-threatening ischemia in diabetics: a retrospective study - Zia Ur Rehman (Journal of the Pakistan Medical Association, 2021)
Objective: To assess number of limb salvaged among diabetic patients with chronic limb-threatening ischemia after infra-inguinal bypass surgeries at low to middle income country (LMIC) hospital. Methods: It was a retrospective chart review of the diabetic patients who underwent infra-inguinal bypass for lower leg revascularization for chronic limb-threatening ischemia at the Section of Vascular Surgery, Aga Khan University Hospital, Karachi (Pakistan) from Jan 2008 till April 2019. Results: Thirty two patients met the inclusion criteria. The mean age was 62.5 ±7.3 years and 18 (56.3%) were male. Ten (31.3%) patients presented with rest pain, 13(40.6%) with gangrene and 9 (28.1%) patients presented with non-healing ulcer. The most common inflow site was common femoral artery 20 (62.5%). The most frequent outflow sites were above and below knee popliteal arteries; 10 (31.3%) patients each. Twenty (62.5%) patients had suitable veins for reconstruction with autologous graft. The limb salvage rate was 90.6%. Three (9.4%) patients had nonfatal MI. There was no perioperative mortality. Conclusion: Diabetic patients with chronic limb-threatening ischemia had salvage rate of 90.5% after infra-inguinal bypass surgeries in our set up comparable to those described in literature. Keywords: Diabetes mellitus, diabetic foot, arteriopathy, critical limb ischemia, amputation. Continuous...